Survival Status and Predictors of Mortality Among Low-Birth-Weight Neonates Admitted to the Neonatal Intensive Care Unit at Felege Hiwot Comprehensive Specialized Hospital, Bahir Dar, Ethiopia, 2020 - Woelile TA; Kibret GT; Workie HM; Amare AT; Tigabu A; Aynalem YA; Chanie ES; Birlie TA (Dove Medical Press, 2021)
Tamiru Alene Woelile,1 Getasew Tesfa Kibret,2 Hailemariam Mekonnen Workie,2 Abraham Tsedalu Amare,3 Agimasie Tigabu,3 Yared Asmare Aynalem,4 Ermias Sisay Chanie,5 Tekalign Amera Birlie3 1Department of Pediatrics and Neonatal Nursing, Wolaita Sodo University, Sodo, Southern Nation and Nationalities of Ethiopia, Ethiopia; 2Department of Pediatrics and Child Health Nursing, Bahir Dar University, Bahir Dar, Amhara, Ethiopia; 3Department of Adult Health Nursing, Debre Tabor University, Debra Tabor, Amhara, Ethiopia; 4Department of Nursing, Debre Berhan University, Debre Berhan, Amhara, Ethiopia; 5Department of Pediatrics and Child Health, Debre Tabor University, Debre Tabor, Amhara, EthiopiaCorrespondence: Tamiru Alene WoelilePediatrics and Neonatal Nursing at Wolaita Sodo University, Wolaita, EthiopiaEmail tamirualene1212@gmail.comAbraham Tsedalu AmareAdult Health Nursing at Debre Tabor University, Debre Tabor, EthiopiaEmail tsedalu136@gmail.comBackground: Low birth weight neonates are subjected to different comorbidities due to anatomical and physiological immaturity. Globally, 60- 80% of neonatal mortality was due to low birth weight. Hence, this study aimed to assess the survival status and predictors of mortality among low birth weight neonates.Methods: An institutional-based retrospective cohort study design was conducted among 718 low birth weight neonates admitted to the neonatal intensive care unit from January 1, 2017, to December 30, 2019, at Felege Hiwot Comprehensive Specialized Hospital. Data were entered into Epi data version 3.1 and analyzed with STATA version 14. Kaplan-Meier curves together with a Log rank test were used to estimate the survival time and showed the presence of differences among groups. Cox proportional-hazard regression was used to estimate the hazard ratio at the 5% level of significance to determine the net effect of each explanatory variable on survival status.Results: The overall incidence density was 35.3 per 1000 person-day observations (CI: 30.8 − 40.6) with 5715 follow-up days. Deliveries outside the health institution [AHR; 2.31 (95% CI: 1.20- 4.42)], maternal age < 18 years [AHR; 3.08 (95% CI: 1.64- 5.81)] and maternal age > 35 years [AHR; 3.83 (95% CI: 2.00- 7.31)], neonatal sepsis [AHR; 2.33 (95% CI: 1.38- 3.94)], neonatal respiratory distress syndrome [AHR; 1.92 (95% CI: 1.27- 2.89)], necrotizing enterocolitis [AHR; 3.09 (95% CI: 1.69- 5.64)] and birth weight < 1000 gm [AHR; 3.61 (95% CI: 1.73- 7.55)] were found to be significant predictors.Conclusion: This study showed that two of the seven low birth weight neonates died during the follow-up period. Therefore, it is better for health care providers and other stakeholders to focus more on early diagnosis and management of low birth weight neonates with sepsis, respiratory distress syndrome, necrotizing enterocolitis and counseling mothers on the risk of having a child in early and old age.Keywords: low birth weight, incidence density, survival status, predictors, Ethiopia